PREPOSITIONAL INCORPORATION IN TOBA BATAKNESE LANGUAGE - Juni Agus Simaremare; Mulyadi Mulyadi (UIN Raden Mas Said Surakarta, 2025)
The purpose of this study is to describe the process of combining prepositions, the rules of combining prepositions, and the forms of prepositions in the Toba Bataknese language. This study used a descriptive-qualitative method whose data are in the forms of texts. The techniques for data analysis include removal, replacement, insertion of reversals, and changes occurrence. The results; of this study; indicate that; the combination of prepositions in Toba Bataknese language can be seen from the movement of prepositions in verbs. The emergence of the suffixes -i and -hon in verbs has changed the argument structure of intransitive verbs into transitive verbs. Likewise, transitive verbs change into ditransitive verbs. The changes in the structure of the verb arguments consist of (1) Subj - V (intr) - Obl à Subj - V (tr) - Obj; (2) Subj - V (tr) - Obj - Obl à Subj - V (dtr) - Obj - Cho. The prepositional forms combined with Toba Bataknese verbs can be divided into two types, namely (1) prepositional forms that change into the suffix -i and (2) prepositional forms that change into the suffix -hon. The prepositional forms that change into the suffix -i in the birth structure are di (in) and tu (to), while the prepositional forms that change into the suffix -hon are tu (to/for) and sian (from).